(untitled) (Medico Legal Update, 2020)
Jaundice is the greatest common situation that needs medicinal care in neonates, which present as yellow coloration of the skin and sclera related to accumulation of unconjugated bilirubin which was considered a neurotoxic to cause brain death (Kernicterus). The Aim of this study to identify the effect of successful breast feeding on neonatal hyperbillirubinemia. Material & method: Design a descriptive design was conducted through a period of study .The sample & setting: were taken accidentally from (250) mothers who had children under one year from practicing breast feeding from Babel maternity and pediatric hospital. Data collection were collected through structured interview and application of the questionnaire with mothers regarding their early achievement of breast fed their jaundiced .Self-administered instrument which takes about 30 minutes. Data analysis: data analyzed the equal number of mother’s age were (43.2%) who were aged (26 - 31) ,with majority (47.2%) of the sample were not educated , therefore that (92.0%) were not working . The researchers recommend educational booklets construction concerning the ten steps of successful breast feeding.